Assessments of joint hydrological extreme risks in a warming climate in China. (6th August 2015) - Leng, Guoyong; Tang, Qiuhong; Huang, Shengzhi; Zhang, Xuejun; Cao, Junjun
ABSTRACT: Understanding how hydrological extremes would respond to global warming and its associated uncertainties is important for better designing mitigation and adaption strategies to cope with global change. Very few works have investigated the changes in future hydrological extremes and, especially, the more devastating joint hydrological extremes over China. In this article, two combinations of joint extremes [i.e. high runoff/high soil moisture (HRHS) and low runoff/low soil moisture (LRLS)] are designed for analysis. To derive the scenarios of hydrological conditions, the bias‐corrected daily climate projections from five global circulation models (GCMs) under the historical and Representative Concentration Pathways 8.5 (RCP8.5) emission scenarios are used to drive the calibrated Variable Infiltration Capacity (VIC) model from 1951 to 2099 over China. Results show notable increase of occurrence of HRHS in Northeast China, LRLS in Northwest and South of China under 2 °C global warming. The spatial pattern of changes in joint extremes tends to remain stable with global temperature increase up to 3 °C. Compared with the individual extreme risk, joint extreme are much more concentrated in Northwest and South China and the magnitude of changes is several times larger. Larger areas experiencing changes are found when using lower standards of extreme definition. Because hydrological regime may change gradually in response to climate change, the threshold derived from present regime may lead to misrepresentation of extreme risk analysis. This was demonstrated by the ten times smaller magnitude of changes when adopting the updated transient threshold representing the changing hydrological regime, thus providing a low‐boundary of potential changes in extremes. Our results highlight the importance of considering the changing hydrological regime in addition to choosing various levels of threshold for extreme definition in order to cover the full range of possible extreme changes in a warming climate.